Promise Me Sunshine : a novel - Bastone, Cara (New York, NY : The Dial Press, 2025)
"Lenny's a bit of a mess at the moment. Her best friend, Lou, recently passed away after her battle with cancer, and her death has left Lenny feeling completely lost. She's avoiding her concerned parents, the apartment she shared with Lou, and the list of things she's supposed to do to help her live again. The only thing she can do is temporary babysitting gigs, and luckily, she just landed a great one, helping overworked, single mom Reese and her precocious daughter, Ainsley. It's not perfect: Ainsley's uncle, Miles, always seems to be around, and is kind of... a huge jerk. But if Lenny acts like she has it all together, maybe no one will notice she's falling apart. Miles sees right through her though. Turns out, he knows a lot about grief and, surprisingly, he offers her a proposition. He'll help her complete everything on her "live again" list if she'll help him connect with Ainsley and overcome his complicated relationship with Reese. Lenny doubts anything can fill the Lou has left behind, but as they begin to spend more time together, Lenny is surprised to discover that, sometimes, you have to lose everything in order to find yourself, and love, again"--.
new book 2025 spring.
Keywords: Best friends; Grief; Death; Man-woman relationships; Novels; Romance fiction